The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1371/journal.pone.0155358
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Genetic Analysis of a Novel Light-Dependent Lesion Mimic Mutant, lm3, Showing Adult-Plant Resistance to Powdery Mildew in Common Wheat

Abstract: Lesion mimics (LMs) that exhibit spontaneous disease-like lesions in the absence of pathogen attack might confer enhanced plant disease resistance to a wide range of pathogens. The LM mutant, lm3 was derived from a single naturally mutated individual in the F1 population of a 3-1/Jing411 cross, backcrossed six times with 3–1 as the recurrent parent and subsequently self-pollinated twice. The leaves of young seedlings of the lm3 mutant exhibited small, discrete white lesions under natural field conditions. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 77 publications
2
32
5
Order By: Relevance
“…As several lesion mimic mutants exhibit resistance to pathogen attacks, particularly to biotrophs (Mock and Grimm, 1997;Kruse et al, 1995;Molina et al, 1999;Tang et al, 2012;Wang et al, 2016), we investigated whether Ghlmm has acquired an elevated resistance to the V. dahliae infection. Infection assays showed that Ghlmm reached the resistance level of H7124, a resistant control for V. dahlia infection, while W0 was as susceptible as Jun1, a susceptible control for V. dahliae Note that the wild-type GhLMMD protein could be expressed and purified from E. coli, while no mutant GhLMMD protein was expressed after induction.…”
Section: The Lesion Mimic Mutants Of Cotton Confer Resistance To V Dmentioning
confidence: 99%
See 1 more Smart Citation
“…As several lesion mimic mutants exhibit resistance to pathogen attacks, particularly to biotrophs (Mock and Grimm, 1997;Kruse et al, 1995;Molina et al, 1999;Tang et al, 2012;Wang et al, 2016), we investigated whether Ghlmm has acquired an elevated resistance to the V. dahliae infection. Infection assays showed that Ghlmm reached the resistance level of H7124, a resistant control for V. dahlia infection, while W0 was as susceptible as Jun1, a susceptible control for V. dahliae Note that the wild-type GhLMMD protein could be expressed and purified from E. coli, while no mutant GhLMMD protein was expressed after induction.…”
Section: The Lesion Mimic Mutants Of Cotton Confer Resistance To V Dmentioning
confidence: 99%
“…Several lesion mimic mutants have been reported in model plant Arabidopsis (Arabidopsis thaliana; Ishikawa et al, 2001;Quesada et al, 2013) as well as in cultivated crops such as maize (Zea mays; Hu et al, 1998), rice (Oryza sativa; Sun et al, 2011), and wheat (Triticum aestivum; Wang et al, 2016). Among them, about 40 genes controlling the lesion mimics have been isolated (Bruggeman et al, 2015).…”
mentioning
confidence: 99%
“…The constant studies of LMMs have greatly deepened our understanding of the regulatory mechanisms governing PCD, including chloroplast activity and light energy capture, sphingolipids and fatty acids, membrane trafficking, secondary messengers, and transcription control (Moeder & Yoshioka, ; Bruggeman et al ., ).In rice, multiple biochemical events and signaling pathways are involved in the progress of lesion mimics and PCD execution, including tetrapyrrole biosynthesis (Sun et al ., ), carbohydrate metabolism (Vega‐Sanchez et al ., ), ABA signal (Wang et al ., ,b,c), protein phosphorylation mediated by wall‐associated kinase (Harkenrider et al ., ) and Ser/Thr protein kinase (Takahashi et al ., ), protein ubiquitination via E3 ubiquitin ligase (Zeng et al ., ; Liu et al ., ), vesicular trafficking (Qiao et al ., ), transcription control (Yamanouchi et al ., ), RNA splicing (Chen et al ., ), and ATPase‐mediating cellular activities (Fekih et al ., ). Moreover, the lesion occurrence has been reported to be light‐dependent in different plants (Muhlenbock et al ., ; Wang et al ., ,b,c, ), showing that light is an important stimulus inducing lesion formation.…”
Section: Introductionmentioning
confidence: 96%
“…PCD is essential for plant developmental programs and response to environmental stimuli by eliminating unnecessary cells; the process is finely controlled by multiple signaling molecules such as reactive oxygen species (ROS) and various hormones (Dominguez & Cejudo, ; Petrov et al ., ; Serrano et al ., ; Van Hautegem et al ., ; Van Durme & Nowack, ). For example, the occurrence of lesions and PCD is associated with massive ROS accumulation in rice (Kojo et al ., ; Chen et al ., ), wheat (Wang et al ., ), and Arabidopsis (Chai et al ., ). Thus, LMMs are valuable materials for unraveling the signaling pathways and molecular mechanisms governing the PCD execution in plant (Moeder & Yoshioka, ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the accumulation of reactive oxygen species (ROS) and the activities of ROS-related enzymes, such as superoxide dismutase (SOD) and catalase (CAT), play important roles in the formation of the lesion mimic phenotype [17,18]. For example, the light-dependent LMM, lm3, shows adult-plant resistance to powdery mildew in common wheat because of the accumulation of ROS [19]. Furthermore, the LMM, lmm6, was more resistant than the wild type (WT) to rice blast fungus Magnaporthe grisea, and had a higher accumulation of ROS and a lower SOD enzyme activity [20].…”
Section: Introductionmentioning
confidence: 99%